Serum heat inactivation diminishes ApoE-mediated uptake of D-Lin-MC3-DMA lipid nanoparticles - Demian van Straten; Luuk van de Schepop; Rowan Frunt; Pieter Vader; Raymond M. Schiffelers (Beilstein Journal of Nanotechnology)
Nanoparticles play a crucial role in drug delivery research. The protein corona that develops on the surface of nanoparticles after administration has garnered substantial attention due to the significant effects it has on their performance. Lipid nanoparticles (LNPs) depend on protein corona formation to mediate their targeting. Such protein–nanoparticle interactions are often initially studied using in vitro cellular models aiming to eventually understand biodistribution and cargo delivery efficiency of the LNPs in vivo. For in vitro cell culture, fetal calf serum (FCS) is supplemented to culture media to provide nutrients and promote cell viability and growth. Heat inactivation of FCS is often performed to prevent complement system activation. However, the effect of this process on protein corona formation and, in turn, LNP functionality is unclear. Here, we investigated the effects of serum heat inactivation on protein corona formation on LNPs containing D-lin-MC3-DMA (MC3) or C12-200 (C12) ionizable lipids. Cellular uptake and siRNA delivery efficiency of the LNPs were determined in media containing untreated or heat-inactivated serum. Mechanistically, we found that apolipoprotein E, a protein corona component that is crucial for MC3 LNP tropism, displayed reduced stability and functionality upon heat inactivation of FCS, thereby negatively influencing uptake and cargo delivery of MC3 LNPs, but not C12 LNPs. Our results underline the importance of overlooked factors in in vitro experiments that can inadvertently affect LNP performance. These findings can help to improve protocols to study protein corona formation in vitro and prevent bias in LNP development.